PENANGANAN KEPOLISIAN TERHADAP TINDAK PIDANA SUAP MENURUT UNDANG-UNDANG NOMOR 20 TAHUN 2001 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI : The Police Handling Of Bribery Offenses According To Law Number 20 Of 2001 On The Eradication Of Corruption Offenses - Dian Adriawan Daeng Tawang; Rini Purwaningsih; Siti Nurbaiti (Faculty of Law, Trisakti University, 2023)
The eradication of corruption is one of the priorities for the Indonesian state in an effort to achieve a clean and corruption-free government. Currently, the regulation governing the eradication of corruption is Law Number 20 of 2001 concerning the Eradication of Corruption. One form of criminal act regulated in this law is bribery. Bribery is a serious threat to the Indonesian state. This crime can damage the judicial system, hinder development, and create social injustice. Therefore, the eradication of bribery must be carried out seriously and firmly by all parties, including the government, law enforcement, and the community. Some efforts that can be made are establishing institutions or special agencies in charge of handling bribery cases, providing education and training for law enforcement, and raising public awareness about the dangers of the crime of bribery, particularly law enforcement officers. The investigation and prosecution of bribery crimes are carried out by law enforcement agencies, such as police and prosecutors. Article 44 of Law Number 20 of 2001 states that the investigation of corrupt practices is conducted by investigators who meet special qualifications and is carried out firmly, quickly, and professionally. The purpose of this investigation and prosecution process is to uncover the truth about the bribery cases and punish the perpetrators. Keywords:. Police Investigation, Bribery, Corruption